2015: A Transition Year for Pharmaceuticals? - Jean Jacques Vanden Eynde (MDPI AG, 2016)
In this period, I could not start this editorial without wishing all of you a Happy New Year. This is also the opportunity for me to warmly thank, for their confidence, our authors, readers, reviewers, members of the editorial board, sponsors, as well as members of MDPI AG in Basel, Beijing, and Wuhan. [...]